2017
DOI: 10.4236/psych.2017.82016
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors for Basic Numerical and Magnitude Competencies in Preschool Children—Are They the Same or Different regarding Specific Subgroups?

Abstract: Basic numeric competencies in early childhood are found to be good predictors for later mathematical achievement. Therefore, it is of broad interest how specific predictors in early childhood, which are held responsible for a better arithmetic development later on, can be found. Our study aims to conduct more information to this topic and hence to extract factors that can already predict the basic numerical and magnitude competencies in preschool. Based on a sample of 188 preschoolers from 26 different kinderg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…However, in the present study, visuospatial abilities were not a relevant predictor for children’s understanding of the cardinality of small numbers. This seems to be in contrast to the findings of Pixner et al (2017) who observed an association between visuospatial abilities and basic numerical competencies in kindergartners. Yet, a closer look at the study reveals at least two possible reasons for these differences.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, in the present study, visuospatial abilities were not a relevant predictor for children’s understanding of the cardinality of small numbers. This seems to be in contrast to the findings of Pixner et al (2017) who observed an association between visuospatial abilities and basic numerical competencies in kindergartners. Yet, a closer look at the study reveals at least two possible reasons for these differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, these differential results may be related to the age of the present sample. Children in our study were on average 1.6 years younger than those assessed in the study of Pixner et al (2017) . Therefore, one might speculate that visuospatial abilities only gain significance for numerical development at a later point in time.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…They use their hands to touch objects during counting, but they also use their fingers as a counting aid when learning about number words and remembering the counting sequence (Lafay et al, 2013). As an important basic numerical skill, counting is strongly associated with children's development of mathematical skills later in life (Pixner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%